A new endemic clove tree pest of Cryptophasa Lewin, from Sangihe Island, Indonesia (Lepidoptera: Xyloryctidae) - Watung, Jackson F; Tairas, Robert W; Kaligis, James B; Darmawan, Darmawan; Suwito, Awit; Narakusumo, Raden Pramesa; Encilia, Encilia; Dwibadra, Dhian; Dharmayanthi, Anik Budhi; Sutrisno, Hari (Zootaxa, 2024)
A novel endemic pest of clove tree, Cryptophasa warouwi sp. nov., has been discovered on Sangihe Island. This new species can be distinguished from its closest relative species, C. watungi Sutrisno & Suwito, 2015 which is found in North Sulawesi, by its dark brown straw-coloured wings in both males and females. The most distinctive diagnostic characters of this new species are observed in its genitalia structure: a bent-downward uncus with a strongly sclerotized finger-shaped apex, a bent phallus gradually widened towards coecum, and a double, membranous corpus bursae branching off at mid-ductus corpus bursae of female genitalia. Additionally, DNA barcodes revealed this new species to be embedded among Australian Cryptophasa species despite having fasciculated male antennae that have been considered diagnostic of the genus Paralecta. This suggests that the male antennae may not be a reliable character for separating Cryptophasa from Paralecta. A more comprehensive study including all Cryptophasa and Paralecta will be required to elucidate the definition of each genus. Images depicting both adults and genitalia are provided for this newly recognized species.